1988
DOI: 10.1017/s0033291700009752
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and metabolism of oxygen and glucose in young autistic adults

Abstract: SynopsisRegional cerebral blood flow, oxygen consumption and glucose consumption were measured by positron emission tomography in six young autistic men. No significant differences were found between patients and normal controls for any of the physiological variables. The results do not substantiate the previous finding of glucose hypermetabolism in autism; the likely reasons for the variance in findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…These mean CMR O2 and CMR glc values corresponded to respective mean OGI values of 5.6 ± 0.8 and 5.4 ± 0.3 for the HRRH and V data sets, which are in good agreement with prior results. [37][38][39][40][41] The slightly better regional stability in the V data (versus the HRRH data) was likely because of better spatial resolution in the V data, which were presumably less affected by partial volume effects arising from white matter, which has a much lower average metabolic rate than gray matter and a variable percentage within the image voxels can cause significant rate variations even with a constant rate of gray-matter metabolism. However in some small brain regions the metabolic values varied by as much as 50% from the gray-matter mean (Figure 4).…”
Section: Regional Oxidative Demand For Glutamatergic Activity In the mentioning
confidence: 99%
“…These mean CMR O2 and CMR glc values corresponded to respective mean OGI values of 5.6 ± 0.8 and 5.4 ± 0.3 for the HRRH and V data sets, which are in good agreement with prior results. [37][38][39][40][41] The slightly better regional stability in the V data (versus the HRRH data) was likely because of better spatial resolution in the V data, which were presumably less affected by partial volume effects arising from white matter, which has a much lower average metabolic rate than gray matter and a variable percentage within the image voxels can cause significant rate variations even with a constant rate of gray-matter metabolism. However in some small brain regions the metabolic values varied by as much as 50% from the gray-matter mean (Figure 4).…”
Section: Regional Oxidative Demand For Glutamatergic Activity In the mentioning
confidence: 99%
“…Glucose metabolism has been investigated in individuals with ASD under different states, including awake, asleep and anesthetized. In awake individuals with ASD, glucose metabolism has been investigated when participants were resting or performing a task such as listening to music or performing memory or attention tasks (Hazlett et al, 2004;Haznedar et al, 1997Haznedar et al, , 2000Herold et al, 1988;Horwitz et al, 1988;Rumsey et al, 1985;Siegel et al, 1992). During memory tasks, atypical glucose metabolism was observed in the cingulate, occipital and parietal cortices in individuals with ASD (Hazlett et al, 2004;Haznedar et al, 1997).…”
Section: Glucose Metabolism Using 2-deoxy-2-( 18 F)fluoro-d-glucose (mentioning
confidence: 99%
“…During memory tasks, atypical glucose metabolism was observed in the cingulate, occipital and parietal cortices in individuals with ASD (Hazlett et al, 2004;Haznedar et al, 1997). However, there is no consensus across FDG studies in individuals with ASD, as some studies have found no difference (De Volder et al, 1987;Herold et al, 1988), while others have reported hypometabolism in the thalamus or putamen Haznedar et al, 2006;Siegel et al, 1992) or widespread hypermetabolism (Rumsey et al, 1985). Some of the discrepancies might be attributed to differences in study design, such as differences in age, level of functioning (IQ) and the conditions under which the experiments were carried out (different cognitive and physiological states); however the relationship between "subpopulations" of ASD and FDG has not been reported.…”
Section: Glucose Metabolism Using 2-deoxy-2-( 18 F)fluoro-d-glucose (mentioning
confidence: 99%
“…Herold et al [1988] reported normal glucose and oxidative metabolism, as well as regional cerebral blood flow (rCBF), in a single slice through the basal ganglia and temporal gray matter of eight relatively high-functioning men with autism (ages 21-25) who were studied while listening to music of their choice, compared to eight healthy controls. DeVolder et al [1987] reported normal mean glucose metabolic rates, but increased variability, in 18 autistic children (ages 2-18 years), many of whom were sedated for scanning, compared to six children with varied brain pathology and 15 normal adult controls (who show lower metabolic rates than children) [Chugani et al, 1987].…”
Section: Studies Of Brain Metabolism Using Positron Emission Tomographymentioning
confidence: 99%